СУЧАСНІ МЕТОДИКИ ВИЗНАЧАННЯ ПРОФЕСІЙНОЇ ПРИДАТНОСТІ МАЙБУТНІХ ФАХІВЦІВ - Alekseeva, S (Continuing Professional Education: Theory and Practice, 2019)
In the article the features of diagnostic methods of study of professional suitability of personality are examined in the system of professional selection. It is analyses modern methodologies of determination of professional suitability of future specialists. Methodological requirements are reasonable to methodologies of study of professional suitability. He basic components of professional suitability are certain, namely: professional gift, professional orientation, physiological features, integrity of personality. The process of diagnostics of professional suitability is modeled, that will provide the objective estimation of possibilities and capabilities of personality to mastering of profession, successful professional adaptation and will allow to optimize the rates of the professional becoming of personality